Reverse Evidence System in TPPU and Corruption Criminal Verdict Cases - Kharina Aliyya Putri Widiyawati; Regita Berliana Pangestu; Shafira Eka Putri; Anggi Pertiwi Meliala (President University, 2020)
In the context of criminal law, the burden of proof generally lies with the prosecution. However, in cases of Money Laundering (TPPU) and Corruption, there is a unique phenomenon in the form of a 'reverse evidence system'. This system allows the burden of proof to be shifted to the defendant to prove that the assets or property he owns come from a legitimate source. This phenomenon emerged in response to the difficulty of uncovering the extensive networks and complex methods used by TPPU and corruption perpetrators. Through a literature study, this research explores the origins, legal basis, and implications of applying the reverse evidence system in these cases. The research results show that although this system has advantages in increasing the effectiveness of prosecutions, it also raises controversies related to human rights principles and principles of justice. It is important for legal practitioners to understand the balance between efforts to eradicate crime and protect individual human rights.Keywords: Burden of Proof; Corruption; Human Rights; Money Laundering Crime (TPPU); Reverse Evidence System.